셔레이드 기법이 인물의 성격구축 결정에 미치는 영향 : 영화 "4월 이야기"를 중심으로 - 김성훈; Kim, Seong-Hoon (한국콘텐츠학회 논문지, 12(2), 2012)
With the help of information technology for a film, characteris both the composition of the story and one of the most important elements that lead the story. Character has a close relationship with personality description, and the character's age, background, education, and occupation help decide his or her personality. Charades are important in that by describing a character's psychology using charade techniques, it gives a stronger impression than by describing with merely lines or narration. When a man's thought changes, their behavior changes; when a behavior is repeated, it becomes habit; when a habit is repeated, it becomes nature. The nature is the person's personality, otherwise called character. Therefore, charade techniques describe a character's psychology well, and consequently, it has maintained its importance. Because human nature and in-depth psychological description have a connection with a character's personality development, I would like to discuss the topic through this research. By using Director Shunji Iwai's "April Story" as the text, the effects of charade techniques on a character's personality development in film will be analyzed by seeking and presenting the methodology shown within the work through charade-acting techniques used by the characters for the development of character's personality. 영화에 있어서 등장인물은 곧 영화의 구성이며 이야기를 이끌어 나가는 주요한 요소이다. 인물은 성격 묘사와 밀접한 관계가 있으며 인물의 연령과 배경 그리고 학력, 직업은 성격을 판단하는 자료가 된다. 셔레이드가 중요한 이유는 셔레이드 기법을 쓰면 대사나 나레이션으로 설명하는 것보다도 훨씬 강한 인상으로 인물의 심리를 표현 할 수가 있다. 인간은 생각이 바뀌어야 행동이 바뀌고 행동이 반복되면 습관이 되고 습관이 반복이 되면 성품이 되는 것이다. 성품은 곧 인물의 성격, 캐릭터라 부른다. 셔레이드 기법이 인물의 심리를 잘 표현하는 것이기에 인물의 성격구축에 중요한 축을 유지 하고 있고 인간 심성과 심리적인 심층묘사는 곧 인물의 성격 구축과 일맥상통하는 것이기에 본 연구를 통하여 논의하고자 한다. 이와이 슈운지 감독의 "4월 이야기"를 텍스트로 선택하여 인물들이 행하는 섬세한 셔레이드 연기기법을 통해 인물의 성격을 어떻게 구축하는지의 방법론을 찾아 제시하여 작품 속의 셔레이드 기법이 인물의 성격구축에 미치는 영향을 분석 하겠다.